What's wrong with modern money theory (MMT): A critical primer - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2019)
Recently, there has been a burst of interest in modern money theory (MMT). The essential claim of MMT is sovereign currency issuing governments do not need taxes or bonds to finance government spending and are financially unconstrained. MMT rests on a triad of arguments concerning: (i) the macroeconomics of money financed budget deficits, (ii) the employer of last resort or job guarantee program, and (iii) the history of money. This primer analyzes that triad and shows each element involves suspect economic arguments. That leads MMT to underestimate the economic costs and exaggerate the capabilities of money financed fiscal policy. MMT's analytic shortcomings render it poor economics. However, its simplistic printing press economics is proving a popular political polemic, countering the equally simplistic and wrong-headed household economics of neoliberal austerity polemic.
Keywords: E00; E12; E40; E58; E60; 330; Modern money theory (MMT); budget deficits; job guarantee program